Modern Information Security - Kongratbay, Tlemisov Ilham; Faxratdinovich, Jangabaev Muxtar; Ayxoja uli, Janxojaev; Òserbay uli, Qallibekov U'mitbek (European Journal of Life Safety and Stability (2660-9630), 2023)
This article is about information security.